Anticancer metal-N-heterocyclic carbene complexes of gold, platinum and palladium. (April 2018) - Zou, Taotao; Lok, Chun-Nam; Wan, Pui-Ki; Zhang, Zhi-Feng; Fung, Sin-Ki; Che, Chi-Ming
Highlights: Metal-NHC complexes have their metal centers stabilized under physiological conditions and can exhibit anticancer activity. Metal-NHC complexes having new functionalities can be designed via facile NHC ligand modifications. Au(I)-NHC complexes display thiol reactivity that is tunable by ligand design. Pincer-type Au(III)-containing, Pt(II)-containing and Pd(II)-containing NHC ligands show effective anti-tumor activities. Some luminescent metal-NHCs can be used as molecular probes and for bioimaging. Abstract : Transition metal compounds are a rich source for anticancer drug development. Judicious application of coordination ligands is a critical success factor in the design of effective anti-tumor compounds. N-heterocyclic carbenes (NHC) are stable ligands that have strong donor strengths in stabilizing metal ions and versatility in structural modifications to provide diverse scaffolds for biological molecular targeting. Remarkable advances have been achieved in the development of metal NHC complexes as anticancer as well as theranostic agents. NHC complexes of gold, platinum and palladium have been designed to elicit potent cancer cell cytotoxicity, effective anti-tumor activities in animal models as well as selective binding to molecular targets (e.g. protein thiols, DNA G-quadraplexes, mismatched DNA). The mechanisms of action of some of these complexes have been elucidated.